Accountability and media literacy mechanisms as a counteraction to disinformation in Europe. (1st September 2019) - Richter, Andrei
Today's digital media environment and the widespread proliferation of propaganda-driven disinformation confront professional media entities with numerous new challenges, and place a heavier burden on journalists and standards of journalism. This article reviews the pursuit for truth as a basic principle that stays for professional journalism, and further examines the current good practices on self-regulation of disinformation in Europe, in particular the rulings of the Advisory Commission on Counteracting the Propaganda in Eastern Europe. It takes a look at the recent efforts by media associations and companies to self-regulate and to promote media literacy as an antidote to disinformation, as well as the relevant intergovernmental policies in Europe. The conclusions provide recommendations on fine-tuning existing mechanisms to counteract disinformation through media accountability and literacy.